PREVENTION OF DEVIANT AND DELIVEN BEHAVIOR (American Journal of Pedagogical and Educational Research, 2025)
The article focuses on references to deviant and delinquent behavior classification among minors. Signs of such behavior, factors of origin, positive norms were analyzed, practical recommendations and psychodiagnostic methodology were presented. The article is intended for psychologists, educators, representatives of the social sphere, parents.